KOMUNIKASI TENTANG KEPANGKATAN DOSEN FIKOM UPDM (B) - Sundoro, Panggih (Universitas Prof. Dr. Moestopo (Beragama), 2006)
This happened to Moestopo University in particular the Faculty of Communication, before year 1990 was still predominated among the academic categories by only and handful qualified lectures. The majority who spend much of their day as governmental officials and who should perhaps be classified as- academic staff as well without academic_rank.Because the University reflects the intelectual and educational status of the society that spawn them, it comes as no surprise that in the terms of the academic model, persons who give lectures legitimately altared to the convensational Conception in advancement to rise ranks in lecturership. After years of the Communication Faculty Moestopo University as an educational institution were marked by experimentation with the academic content and forms. The first challengence was to rise ranks legitimately.First of all the latest trend in its education system, is putting the lecture on communication and information sciences. The impact of these changes, I hope can solved the problems of to rise ranks legitimately and objective.